My pal Trigger [videorecording (DVD)] - Rogers, Roy, 1911-1998; Rogers, Dale Evans; Hayes, George, 1885-1969 (Alpha Video Distributors, 2003)
Roy and the bad guys both want to mate their mares with a prize stallion which is owned by Gabby. One of villains accidentally kills the stallion. Roy's mare has a foal that grows up to be Trigger.